Agricultural Machinery Adoption and Farmers’ Well-Being: Evidence from Jiangxi Province - Zhihua Wu; Bing Liao; Qing Fu; Chongyi Qi; Wenmei Liao (Agriculture)
As a cornerstone of agricultural modernization, agricultural mechanization plays a pivotal role in driving rural revitalization and establishing agricultural competitiveness. Drawing upon the theoretical framework of happiness economics, this study investigates the impact, mechanisms, and heterogeneous effects of agricultural machinery adoption on farmers’ subjective well-being, utilizing comprehensive household survey data collected from Jiangxi Province in July 2023. The empirical results demonstrate a significant positive correlation between agricultural machinery adoption and farmers’ subjective well-being, a finding that remains robust after addressing endogeneity concerns through instrumental variable approaches. The mechanism analysis reveals that the enhancement of well-being is primarily mediated through facilitated transitions to non-agricultural employment. The purpose of the mechanism analysis is to explain why agricultural mechanization adoption improves farmers’ subjective well-being. This analysis finds that agricultural mechanization adoption improves farmers’ subjective well-being by helping them transition to non-agricultural employment more smoothly. Furthermore, heterogeneity analysis indicates that the beneficial effects are more substantial among male farmers, individuals with higher educational attainment, and younger demographic groups. These findings suggest that policy interventions should focus on enhancing innovation in agricultural machinery technology, optimizing subsidy programs for agricultural equipment, improving rural education systems, and facilitating the structural transformation of rural labor markets.